Effect of CPAP on airway reactivity and airway inflammation in children with moderate–severe asthma. Issue 4 (16th November 2018) - Praca, Eduardo; Jalou, Hasnaa; Krupp, Nadia; Delecaris, Angela; Hatch, Joseph; Slaven, James; Gunst, Susan J.; Tepper, Robert S.
ABSTRACT: Background and objective: Asthma is characterized by airway hyperreactivity and airway inflammation. We previously demonstrated that adults with mild well‐controlled asthma exhibited a marked decrease in airway reactivity (PC20 increased >2‐fold) after using nocturnal continuous positive airway pressure (CPAP) for 1 week. If CPAP produces a similar suppression of airway reactivity in children with moderate–severe asthma, who require chronic use of corticosteroids, then this non‐pharmacological therapy might provide a beneficial alternative or supplemental therapy in these subjects. Methods: Children aged 8–17 years with moderate–severe asthma were treated with 4 weeks of nocturnal CPAP (8–10 cm H2 O) or sham CPAP (<2 cm H2 O). Adherence was monitored with a modem installed in the equipment or by memory cards. Airway reactivity, assessed by methacholine bronchial challenge, was measured prior to and following treatment. Results: The percentage of subjects adherent to treatment was similar in both groups (19/27 CPAP vs 19/28 sham, ~70%). There was a tendency for PC20 to increase with treatment in both groups (3.0–5.3 mg/mL CPAP vs 3.2 to 4.3 mg/mL sham, P = 0.083); however, the change did not differ significantly between groups ( P = 0.569). Conclusion: We found that the 4‐week treatment with nocturnal CPAP did not produce a twofold suppression of airway reactivity in children with moderate–severe asthma. Abstract : We compared 4 weeks of nocturnal continuous positive airway pressure (CPAP) versus sham to suppress airway reactivity and inflammation in children with moderate–severe asthma. There were no significant differences between treatments. The treatment effect in children with moderate–severe asthma was smaller than previously reported in adults with mild well‐controlled asthma. See related  Editorial